7-Chloro-4-[(E)-2-(4-methoxybenzylidene)hydrazin-1-yl]quinoline monohydrate - Ferreira, M.L.; de Souza, M.V.N.; Howie, R.A.; Tiekink, E.R.T.; Wardell, J.L.; Wardell, S.M.S.V. (International Union of Crystallography, 2010)
The organic molecule in the title hydrate, C17H14ClN3O center dot H2O, has a small but significant twist from planarity, as seen in the dihedral angle of 12.10 (17)degrees between the quinoline and benzene rings. The conformation about the C=N bond is E. Chains along the b axis are formed in the crystal structure aided by water-quinoline O-H center dot center dot center dot N (x 2) and hydrazone-water N-H center dot center dot center dot O hydrogen bonds. Layers of these chains stack along the a axis via C-H center dot center dot center dot pi and pi-pi interactions [ring centroid-ring centroid distance = 3.674 (2) angstrom]. C-H center dot center dot center dot O interactions are also present.